2004
DOI: 10.1099/vir.0.19423-0
|View full text |Cite
|
Sign up to set email alerts
|

A murine oral enterovirus 71 infection model with central nervous system involvement

Abstract: Enterovirus 71 (EV71) infection causes a myriad of diseases from mild hand-foot-and-mouth disease or herpangina to fatal meningoencephalitis complicated with neurogenic pulmonary oedema. Its pathogenesis, especially the CNS involvement, is not clearly understood. The aim of this study was to set up a mouse EV71 infection model with CNS involvement. EV71 virus was administrated orally to neonatal mice. The EV71-infected mice manifested a skin rash at an early stage and hind limb paralysis or death at a later st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
136
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(142 citation statements)
references
References 20 publications
5
136
1
Order By: Relevance
“…In contrast, studies in cynomolgus monkeys and mice revealed that no EV71 replication occurred in the main organs of the animals, except for the CNS. 27,29 However, it can be argued that oral infection with the strain adapted to mice was capable of inducing virus distribution in some organs, including the heart, lungs and kidneys in mice; 32 infection with the ts strain via the intravenous route in cynomolgus monkeys 27 and infection via the intracerebral, intramuscular, intraperitoneal and subcutaneous routes in mice did not yield a similar distribution of the virus. 29 Our results indicate that virus was present in some organs of the monkeys that were infected via the intravenous and intratracheal routes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, studies in cynomolgus monkeys and mice revealed that no EV71 replication occurred in the main organs of the animals, except for the CNS. 27,29 However, it can be argued that oral infection with the strain adapted to mice was capable of inducing virus distribution in some organs, including the heart, lungs and kidneys in mice; 32 infection with the ts strain via the intravenous route in cynomolgus monkeys 27 and infection via the intracerebral, intramuscular, intraperitoneal and subcutaneous routes in mice did not yield a similar distribution of the virus. 29 Our results indicate that virus was present in some organs of the monkeys that were infected via the intravenous and intratracheal routes.…”
Section: Discussionmentioning
confidence: 99%
“…31 Subsequently, the viruses proliferate in these primary organs and directly enter the bloodstream to establish systemic viremia, which is frequently linked to pathogenesis and the further infection of target tissues, such as the CNS and the myocardium. 32,33 In particular, some previous data suggest that poliovirus is not only neuro-tropic but also lymph node tropic. 31 Although many aspects of EV71 pathogenesis are currently unclear, some preliminary human autopsy reports and well-established murine and cynomolgus monkey models have demonstrated that, in some cases, EV71 pathogenesis occurs by causing neurological lesions in the CNS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, EV71 induces skin rash at the early stage and hind limb paralysis or death at the late stage. Oral infection leads to initial replication in the intestine and subsequent spread to various organs such as the spinal cord and the brain stem (8). Intriguingly, EV71 does not facilitate the production of type I interferon (IFN), a family of cytokines involved in first-line defense against virus infection.…”
mentioning
confidence: 99%